Conceptual Analysis of Musyarakah Mutanaqishah Contract and its Implementation in Islamic Banking - Salimatur Rahmah; Anna Zakiyah Hastriana (Al-Hiwalah: Journal of Sharia Economic Law, 2025)
The concept of Musyarakah Mutanaqishah contract is one form of partnership contract in Islamic banking that is rapidly developing as an alternative financing, where the bank and the customer together provide capital for a business and the bank will gradually reduce ownership of the business along with payments by the customer. In this contract, the customer does not only act as a borrower, but also as a partner in sharing profits and losses based on the proportion of each capital contribution. The implementation of Musyarakah Mutanaqishah in Islamic banking provides a solution for financing the purchase of assets such as houses or vehicles while maintaining sharia principles, including the prohibition of usury, gharar, and maysir. In practice, the Musyarakah Mutanaqishah contract is not only beneficial for both parties, but also provides a sense of justice and transparency in transactions. However, the implementation of this contract still faces challenges in terms of operations, regulations, and market understanding that need to be continuously developed in order to maximize its benefits. This article aims to analyze the basic concept of Musyarakah Mutanaqishah, its implementation mechanism in Islamic banking products, as well as the challenges and opportunities faced in its implementation.